Optoelectronic properties and color chemistry of native point defects in Al:ZnO transparent conductive oxide1. Issue 32 (28th August 2015) - Catellani, Alessandra; Ruini, Alice; Calzolari, Arrigo
<x xml:space="preserve">Abstract</x> The effects of native defects (e.g. VO, VZn, H) on the TCO properties and color of an Al:ZnO (AZO) material are investigated using first principles calculations.